No gain without pain education: Improving knowledge and biopsychosocial attitudes and beliefs in a predominantly non‐health‐related undergraduate target audience. (12th March 2022) - Fitzgerald, Kylie; Vaughan, Brett; Devonshire, Elizabeth; Schneider, Carl; Denham, Rebecca
Abstract: Objectives: Chronic pain (CP) impacts individuals and society and is the leading cause of disability globally. Pain education interventions are often evaluated in patients and health professional students, but not in non‐health student groups. Increasing knowledge of pain may facilitate shifts in attitudes and beliefs towards sufferers. We report on changes in pain knowledge, attitudes and beliefs of predominantly non‐health‐related tertiary degree students participating in online education. Methods: Quantitative cohort study design. Students reported demographics and completed the Chronic Pain Myth Scale and 12‐item Neurophysiology of Pain Questionnaire (NPQ) before (T1) and after (T2) the 7‐week online module at The University of Sydney in 2020. Results: Twenty‐two students undertaking predominantly non‐health‐related bachelor's degrees (16.5% response rate, 90.9% female, mean = 19.5 years) participated. NPQ scores increased from 47.3% to 62.9%. Attitudes and beliefs towards biopsychosocial impact improved ( p < 0.027) but not towards individuals suffering from CP or treatment of CP. A negative correlation was found between age and people suffering from CP ( ρ = −0.437, p < 0.042) and age and towards treatment of CP; ρ = −0.556, p < 0.007) at T2. Conclusion: Completing the elective online module resulted in improved knowledge and biopsychosocial attitudes towards CP in this predominantly non‐health cohort, as reported in health and patient cohorts.